A paradigm shift: robotic-assisted vesicovaginal fistula repair in Pakistan - Hamza Bashir; Naveed Ahmed Mahar; Asad Shahzad Hasan (Journal of the Pakistan Medical Association, 2024)
Dear Editor, Vesicovaginal Fistula (VVF) is a serious medical condition that affects women in Pakistan, causing significant suffering. VVF is an abnormal connection between the bladder and the vagina, leading to continuous leakage of urine [1]. The most common cause of VVF in Pakistan is typically attributed to obstetric complications, particularly prolonged or obstructed labour. Pakistan has a relatively high prevalence of VVF, with many women affected by this condition. Factors associated with VVF in Pakistan include early marriage, limited access to healthcare, and inadequate maternal care [2]. VVF not only poses significant physical challenges but also has profound psychosocial effects on affected women. These effects can include stigma, emotional distress, and a loss of self-esteem [3, 4]. VVF repair can be approached through various surgical methods like transabdominal, transvaginal, laparoscopic, and robotic depending on various factors. For a VVF situated low in the pelvis, such as a deep obstetric fistula, the vaginal approach might be feasible. However, the transabdominal approach is always an option when a safe transvaginal fistula repair cannot be granted. This technique provides maximum space for exact and thorough bladder and vaginal wall preparation and easier identification of the scar and fistula tissue. Therefore, an abdominal approach provides a safe basis for complete excision of the inflamed fistula tissue, good bladder wall mobilization, and tension-free bladder closure[5]. Recent advancements in medical technology have revealed the substantial advantages of using robotic-assisted techniques for repairing VVF when compared to traditional approaches [6]. These advantages include a reduction in complications after surgery, a quicker recovery period, higher rates of success, shorter hospital stays, and a decreased likelihood of postoperative issues, all in contrast to conventional open surgical methods. Additionally, robotic surgery offers enhanced precision in intricate procedures, a particularly valuable feature given the challenges involved in the laparoscopic approach. Robotic-assisted surgery provides optimal exposure to the fistula area, facilitating extensive excision of the affected tissue and contributing significantly to the effectiveness of VVF repair. In a groundbreaking development, Pakistan witnessed its first-ever robot-assisted VVF repair using the transabdominal transvesical technique at SIUT CHABLANI MEDICAL CENTRE, SUKKUR in August 2023. This achievement signals a significant advancement towards a less invasive treatment approach. I strongly advocate for the acknowledgment of this milestone by Pakistani policymakers, healthcare institutions, and medical practitioners. ---Continue